Numerical simulations of shallow groundwater flow and heat transport in a continuous permafrost setting under the impact of climate warming - Shojae Ghias, Masoumeh; Therrien, René; Lemieux, Jean-Michel; Molson, John W. H. (Canadian Geotechnical Journal, 2020)
Numerical simulations of coupled groundwater flow and heat transport are used to address how hydrogeological conditions can affect permafrost dynamics. The simulations are based on a 2D vertical-plane conceptual model of a study site at the Iqaluit Airport, Nunavut, Canada, which includes a 50 m deep permafrost terrain with a shallow active layer, overlain by a paved taxiway with winter snow-covered embankments. Coupled groundwater flow and advective-conductive heat transport with freeze-thaw dynamics, temperature-dependent porewater freezing functions and latent heat are included in the model. The simulation results show that a smooth (low-slope) freezing function with a higher residual unfrozen moisture content produced a deeper thaw front compared to that using a steeper freezing function, generating a maximum increase in the depth to permafrost of 17.5 m after 268 years. Permafrost thaw rates in high-permeability zones within a heterogeneous system were also relatively higher compared to an otherwise equivalent homogeneous soil, resulting in a maximum increase of 2.6 m in the depth to permafrost after 238 years. As recharge water cools while flowing along the upgradient permafrost table, advectively driven heat transport is paradoxically shown to temporarily increase the height of the permafrost table in downgradient areas. Des simulations numériques du débit d’eau souterraine couplé et du transport de chaleur sont utilisées pour déterminer comment les conditions hydrogéologiques peuvent affecter la dynamique du pergélisol. Les simulations sont basées sur un modèle conceptuel en deux dimensions à plan vertical d’un site d’étude à l’aéroport d’Iqaluit, au Nunavut, qui comprend un terrain de pergélisol de 50 m de profondeur avec une couche active peu profonde, recouverte d’une voie de circulation pavée. L’écoulement d’eau souterraine couplée et le transport de chaleur par advection–conduction avec la dynamique de gel–dégel, les fonctions de congélation de l’eau interstitielle dépendant de la température et ...